A FEW CHRISTIAN INTERPRETATIONS OF HUMAN HISTORY - Roy, Louis (Science et Esprit, 2023)
This article presents views of universal history taken from the Bible and from two Christian authors. Those religious and theological interpretations of history are characterized by the concern to highlight a factor that is transcendent. This factor is seen as the overall meaning that underpins human existence in our world.